2022
DOI: 10.1002/cbdv.202100775
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Contents, Potential Antioxidant, Anticholinergic and Antidiabetic Properties of Mountain Mint (Cyclotrichium leucotrichum)

Abstract: In the present work, antioxidant and antidiabetic potentials of mountain mint [Cyclotrichium leu-cotrichum (Stapf ex Rech. Fil.) Leblebici] was the first time appraised. In this sense, methanol (MECL) and water (WECL) extracts were obtained from aerial parts of mountain mint (Cyclotrichium leucotrichum) and studied for their antioxidant ability by several bioanalytical assays. Also, their inhibition profiles were realized toward several metabolic enzymes connected to some diseases, including butyrylcholinester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Aloe, 59 mint, 60 banaba, 61 bitter melon, 62 caper bush, 63 cinnamon, 64 cocoa, 65 coffee, 66 fenugreek, 67 garlic, 68 guava, 69 turmeric, 70 tea, 71 walnuts, 72 Shaggy bindweed, 73 Yerba mates , 74 Bambusa tulda , 75 Ficus bengalensis , 76 Ferula orientalis, 77 Gymnema sylvestre , 78 Dioscorea japonica , 79 Artemisia abyssinica , 80 Phaseolus vulgaris , 81 Datura quercifolia , 82 Cassia fistula , 83 Citrus aurantium , 84 Ficus benghalensis , 85 Polygonum aviculare , 86 Allium tuncelianum , 87 Astragalus brachycalyx , 88 Ferulago stelleta , 89 and Rhizophora mucronate 90 are natural sources that contain chemical moieties which are effective against diabetes. 91 However, recent research-based studies showed more aim to develop new drugs that can be provided orally for the therapeutics uses of diabetes disease.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Aloe, 59 mint, 60 banaba, 61 bitter melon, 62 caper bush, 63 cinnamon, 64 cocoa, 65 coffee, 66 fenugreek, 67 garlic, 68 guava, 69 turmeric, 70 tea, 71 walnuts, 72 Shaggy bindweed, 73 Yerba mates , 74 Bambusa tulda , 75 Ficus bengalensis , 76 Ferula orientalis, 77 Gymnema sylvestre , 78 Dioscorea japonica , 79 Artemisia abyssinica , 80 Phaseolus vulgaris , 81 Datura quercifolia , 82 Cassia fistula , 83 Citrus aurantium , 84 Ficus benghalensis , 85 Polygonum aviculare , 86 Allium tuncelianum , 87 Astragalus brachycalyx , 88 Ferulago stelleta , 89 and Rhizophora mucronate 90 are natural sources that contain chemical moieties which are effective against diabetes. 91 However, recent research-based studies showed more aim to develop new drugs that can be provided orally for the therapeutics uses of diabetes disease.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Diabetes treatment includes insulin and non-insulin therapy. [10] Alzheimer's disease (AD) is a neurodegenerative disease noted in elderly populations with dementia, memory loss, and cognitive impairment.. [11] Acetylcholinesterase (AChE) is a key enzyme that hydrolyzes the neurotransmitter acetylcholine at cholinergic synapses in both the peripheral nervous system and the central nervous system. [12,13] The progression of AD has been observed to be complex and associated with multiple cues such as destruction of cholinergic nerves in the brain and decreased acetylcholine (ACh) levels, dyshomeostasis of metal ions, oxidative stress, and accumulation of amiloid-beta (Aβ) plaques, mitochondrial malfunction and others.…”
Section: Introductionmentioning
confidence: 99%
“…It also plays a role in cell adhesion, synaptogenesis, dopamine neuronal activation, proliferation and cell interactions, and formation of amyloid fibers characteristic for Alzheimer's disease (AD), hematopoiesis, and thrombopoiesis. [35,36] The physiological role of butyrylcholinesterase (BChE) is not known exactly, but it has been revealed that high BChE level may be associated with neuropathological lesions developing in Alzheimer's patients and inhibition of this enzyme, which causes an increase in acetylcholine levels in the brain, may be important for the treatment of AD. [37,38] Additionally, α-glucosidase (α-Glu) is an important enzyme involved in the digestion of carbohydrates which converts starch and disaccharides into glucose.…”
Section: Introductionmentioning
confidence: 99%